Are popular books about diet and health written based on scientific evidence? A comparison of citations between the USA and Japan - Fumi Oono; Riho Adachi; Akinori Yaegashi; Madoka Kishino; Risa Ogata; Anna Kinugawa; Ayari Tsumura; Mizuki Suga; Moe Matsumoto; Tomoya Takaoka; Yuya Kakutani; Kentaro Murakami; et al. (Cambridge University Press, 2023)
Abstract Objectives: To describe and compare the references cited in popular books about diet and health between the USA and Japan. Design: Books were selected based on their best-seller rankings in the diet and health category of online bookstores. We identified references throughout all pages of the books and examined the number of references, reference format (identifiable or not) and presence of specific types of references, such as systematic reviews of human research. We compared the characteristics of references between the two countries and examined related factors to citation. Setting: Cross-sectional study. Participants: Books (n 100 in each country). Results: Among 100 books from each country, sixty-five US and sixty-six Japanese books had references. Forty-five US books cited more than 100 references, against only five Japanese books. The number of books that cited systematic reviews of human research differed between the USA (n 49) and Japan (n 9). Additionally, the number of books that provided identifiable information for all references was significantly higher in the USA (n 63) than in Japan (n 42). Books whose first authors have licences of medical doctors were more likely to cite references than those without in both countries. Conclusions: Two-thirds of books about diet and health cited references in both the USA and Japan, but Japanese books cited fewer references and were less likely to cite systematic reviews and provide identifiable references than US books. Further research into the scientific reliability of information in books about diet and health is warranted.